Increase of DNA Methylation at the HvCKX2.1 promoter by terminal drought stress in barley - Surdonja, Korana; Eggert, Kai; Hajirezaei, Mohammad-Reza; Harshavardhan, Vokkaliga; Seiler, Christiane; Von Wirén, Nicolaus; Sreenivasulu, Nese; Kuhlmann, Markus (MDPI, 2017)
Terminal drought stress during grain filling is the major abiotic factor that limits crop yield in barley. The mother plant acclimates to the environment and perceives signals that result in a change of the physiological state within the grain and therefore affect the seed development and germination of the next generation. Small regulatory RNAs have been described to be involved in plant drought stress response by suppressing the respective target genes. Based on their origin and function, these small RNAs are classified as micro RNAs (miRNA), short interfering RNAs (siRNA) or heterochromatic small interfering RNA (hc-siRNA). In addition, 24mer sized hc-siRNAs are associated with RNA directed DNA methylation (RdDM) and transcriptional gene silencing (TGS). The analysis of hc-siRNA by small RNA sequencing in barley caryopses after imposition of terminal drought stress allowed the identification of stress specific 24mers. Based on the sequence homology of the siRNAs to the promoter region of CYTOKININ-OXIDASE 2.1 (HvCKX2.1), this putative target gene was selected for further investigation. Terminal drought stress leads to an increased level of DNA methylation at the HvCKX2.1 promoter and the seeds derived from drought stressed plants showed faster shoot emergence. Accumulation of cytokinin ribosides, which are the known substrates of cytokinin-oxidase, can explain the observed phenotype of faster shoot emergence from seeds of drought stressed mother plants. Analysis of transgenic plants with modulated levels of abscisic acid (ABA) in the grain confirmed the ABA/drought stress responsive ProHvCKX2.1 methylation and correlation with shoot emergence speed.